ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PENGELOLAAN KEUANGAN PRIBADI MAHASISWA PADA MASA PANDEMI COVID-19 - Kusumawati, Dyah (JAB (Jurnal Akuntansi & Bisnis), 2021)
The purpose of this study was to determine the influence of family socio economic status, financial education, spiritual intelligence and social environment on personal financial management during the Covid-19 pandemic in students of the Fakultas Ekonomi dan Ilmu Sosial, Universitas Sultan Fatah Demak. This type of research is explanatory research. The population is all students of the Fakultas Ekonomi dan Ilmu Sosial, Universitas Sultan Fatah Demak. The technique of determining the sample by means of convenience sampling. In this study, the number of samples used was 60 respondents. Data analysis was performed using multiple linear regression analysis techniques. The technique of collecting data through online questionnaires uses a Likert scale. Data sources are primary data and secondary data. The results of this study are the socio economic status of the family and financial education do not have a significant effect on financial management, while spiritual intelligence and the social environment have a positive and significant effect on financial management.Keywords: family socio economic status, financial education, spiritual intelligence, social environment, financial management